ISOLATION, CHARACTERIZATION OF PHYTASE PRODUCING BACILLUS SUBTILLS MTCC NO.9878 FROM THE GUT OF EISENIA FOETIDA - L. VIJAYASAI; K. VIJAYA LAKSHMI; S. K. SHAHEEN; N. D. PRASANNA (The Bioscan, 2011)
17 Bacteria were isolated from earthworm gut (Eisenia foetida). Phytase enzyme activity of the cultures from gut was screened on modified phytase solubulizing medium (MPSM). The result inferred that four isolates PSB1 to PSB4 were strongly positive in enzyme activity than six of other microorganisms while seven isolates were found negative and among all PSB1 isolate which showed maximum activity was characterized as Bacillus subtilis MTCC No. 9878 based on cultural, morphological, physiological and biochemical characterstics.